1997
DOI: 10.1046/j.1365-2036.1997.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Furazolidone, amoxycillin, bismuth triple therapy for Helicobacter pylori infection

Abstract: Background: Metronidazole‐resistant Helicobacter pylori are generally the rule in developing countries such as Colombia. Developing countries need an effective, simple and inexpensive non‐metronidazole therapy for H. pylori infection. Aim: To evaluate the combination of bismuth, furazolidone and amoxycillin for the treatment of H. pylori infection in Colombia. Methods: Thirty patients with histologically documented H. pylori infection received the combination of bismuth subcitrate 240 mg b.d., furazolidone 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 22 publications
0
54
0
Order By: Relevance
“…Asian and European studies have reported a relatively high incidence of adverse effects (31.4%-35%) [10,24,25] . Conversely, two South American [26,27] studies have shown fewer undesirable symptoms when compared to the previously mentioned studies. In the present study, despite a comparable incidence of adverse effects during treatment, only three patients had severe symptoms demanding treatment discontinuation.…”
Section: Discussionmentioning
confidence: 86%
“…Asian and European studies have reported a relatively high incidence of adverse effects (31.4%-35%) [10,24,25] . Conversely, two South American [26,27] studies have shown fewer undesirable symptoms when compared to the previously mentioned studies. In the present study, despite a comparable incidence of adverse effects during treatment, only three patients had severe symptoms demanding treatment discontinuation.…”
Section: Discussionmentioning
confidence: 86%
“…Furazolidone, a monamine oxidase inhibitor, interacts with many drugs and foods. Adverse effects of furazolidone include nausea, vomiting, headache, tachycardia, and hypertension [104,105].…”
Section: Treatment Of H Pylori Infectionmentioning
confidence: 99%
“…Clinical trials have demonstrated that triple therapies involving furazolidone (including omeprazole, clarithromycin, and furazolidone regimens) are able to achieve a high cure rate of H. pylori, and such regimens may prove particularly useful in areas where the prevalence of metronidazole-resistant strains is high (10,33,46,57). The clinical evaluation of nitrofurantoin has been limited to studies in which the agent was given either as monotherapy or in combination with bismuth subsalicylate and not as part of a triple-agent regimen (4,21,24,39,44).…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that this enzyme reduces the nitro group of metronidazole to active metabolites that are toxic to the bacterium and that resistance arose from mutational inactivation of the underlying gene, rdxA (HP0954 in the H. pylori genome database [49]). Subsequent studies have suggested that, while the development of metronidazole resistance in H. pylori is highly associated with mutational inactivation of the rdxA gene, other mechanisms of resistance are likely to exist in this bacterium (26,48 The nitrofuran group of compounds, which includes furazolidone and nitrofurantoin, appears a particularly promising source of alternative agents for metronidazole in H. pylori eradication regimens (7,46,57). Like that of the 5-nitroimidazoles, the biological activity of these nitroaromatic compounds is largely derived from reductive metabolism of the parent compound's nitro moiety by oxygen-insensitive nitrore-ductases (2,36,55).…”
mentioning
confidence: 99%
See 1 more Smart Citation